CAUSES AND CURRENT STATE OF THE ENERGY CRISIS IN EUROPEAN COUNTRIES - Kogut-Ferens O.І.; Masevych , A.L. (The actual problems of regional economy development, 2023)
The geopolitical situation in the world has always had a direct impact on the global energy market and energy trade. In recent years, the energy situation in Europe has been deteriorating significantly due to a series of crisis events that have shaken the world. The current energy crisis is perhaps the most important problem not only for Ukraine but for the whole world. It is also a global environmental problem. Now, more than ever before, all world leaders and international organisations are concerned about energy supplies and the energy situation in the world as a whole. To solve the problem, it is necessary to understand the causes of the energy crisis and its current state. Therefore, the purpose of this article is to study the stages and causes of the energy crisis and to characterise its current state in European countries. A number of works by such well-known domestic and foreign scholars as S. Kondratov, Yu. Skaletsky, V.I. Kravtsov, D.S. Biryukov, R. Eden, L. Worrell, etc. The article examines the causes of the energy crisis in Europe and the role of quarantine restrictions related to the Covid-19 pandemic. The author examines how the situation in the energy markets has changed since the beginning of the full-scale invasion of Ukraine. An analysis of price changes in the energy market for producers and consumers in the EU during 2021-2023 is carried out. The author considers what measures the EU countries are taking to normalise the situation and overcome the consequences of the energy crisis. The article analyses the development of the LNG market as an alternative to natural gas supplies from Russia, examines the increase in imports from the United States and the expansion of LNG production infrastructure in the European Union. The introduction of alternative energy is considered as a promising way out of the energy crisis. The study shows that Europe's energy system is currently experiencing a large-scale crisis due to quarantine restrictions and the unstable political situation in the world. It is proved that the energy system is also undergoing large-scale transformations due to the refusal to import Russian energy resources.